Automated manufacturing and characterization of clinical grade autologous CD20 CAR T cells for the treatment of patients with stage III/IV melanoma - Aleksandrova, Krasimira; Leise, Jana; Priesner, Christoph; Aktas, Murat; Apel, Michael; Assenmacher, Mario; Bürger, Iris; Richter, Anne; Altefrohne, Pia; Schubert, Christine; Holzinger, Astrid; Barden, Markus; et al. (Frontiers in Immunology, 2024)
Point-of-care (POC) manufacturing of chimeric antigen receptor (CAR) modified T cell has expanded rapidly over the last decade. In addition to the use of CD19 CAR T cells for hematological diseases, there is a growing interest in targeting a variety of tumor-associated epitopes. Here we report the manufacturing and characterization of autologous anti-CD20 CAR T cells from melanoma patients within phase I clinical trial (NCT03893019). Using a second-generation lentiviral vector for the production of the CD20 CAR T cells on the CliniMACS Prodigy® we demonstrated consistency in cell composition and functionality of the products manufactured at two different production sites. The T cell purity was >98.5%, a CD4/CD8 ratio between 2.5 and 5.5 as well as transduction rate between 34% and 61% on day 12 (harvest). Median expansion rate was 53-fold (range 42-65-fold) with 1.7-3.8×10 9 CAR T cells at harvest, a sufficient number for the planned dose escalation steps (1×10 5 /kg, 1×10 6 /kg, 1×10 7 /kg BW). Complementary research of some of the products pointed out that the CAR+ cells expressed mainly central memory T cell phenotype. All tested CAR T cell products were capable to translate into T cell activation upon engagement of CAR target cells, indicated by the increase in pro-inflammatory cytokine release and by the increase in CAR T cell amplification. Notably, there were some inter-individual, cell-intrinsic differences at the level of cytokine release and amplification. CAR mediated T cell activation depended on the level of CAR cognate antigen.In conclusion, the CliniMACS Prodigy® platform is well suited for decentralized POC manufacturing of anti-CD20 CAR T cells and may be likewise applicable for the rapid and automated manufacturing of CAR T cells directed against other targets.